Impact of Atorvastatin Treatment in First‐Degree Relatives of Patients With Premature Coronary Artery Disease With Endothelial Dysfunction: A Double‐Blind, Randomized, Placebo‐Controlled Crossover Trial. Issue 8 (10th June 2013) - Hong, Sung‐Jin; Chang, Hyuk‐Jae; Park, Sungha; Kang, Dae Ryong; Shin, Sanghoon; Cho, In‐Jeong; Shim, Chi Young; Hong, Geu‐Ru; Ha, Jong‐Won; Chung, Namsik
Abstract Background A family history of premature coronary artery disease (CAD) is a well‐known risk factor for cardiovascular events. Hypothesis Atorvastatin may improve endothelial dysfunction (ED) in the first‐degree relatives (FDRs) of patients with premature CAD with ED. Methods Thirty‐five FDRs (median age, 52 years [interquartile range (IQR), 46–57 years], 21 male) of patients with premature CAD with ED were recruited in a prospective trial with a crossover double‐blind design: 6 weeks of treatment with atorvastatin 40 mg/day followed by placebo, or vice versa. After each treatment, the digital pulse wave amplitude was determined by EndoPAT to obtain the reactive hyperemia index (RHI), a measure for endothelial function. The primary outcome was the difference of RHI between atorvastatin and placebo treatment. Results Low‐density lipoprotein cholesterol was lower after atorvastatin compared with placebo treatment (124 [102–145] mg/dL vs 67 [50–73] mg/dL, P < 0.001). However, RHI was not different after atorvastatin compared with placebo treatment (1.9 [1.5–2.4] vs 1.9 [1.6–2.2], P = 0.902). Also, the augmentation index was similar after each treatment. These results were observed both in subjects who had indications for statin treatment (31%) and those who did not (69%) according to National Cholesterol Education Program Adult Treatment Panel III guidelines. Conclusions Despite improvement in the lipid profile, atorvastatin failed to improve ED in the FDRs of patients with premature CAD with ED. Although we identified those with ED in FDRs of patients with premature CAD as a high‐risk group for future cardiovascular events, atorvastatin treatment may not be a beneficial primary prevention strategy for this population.